A study on the application of Kovach's motivational theory among employees at Petronas Refinery (Malacca) Sdn. Bhd. / Norisah Puteh - Puteh, Norisah (2004)
Motivation is an important tool that is often under-utilised by the managers in today's workplace. Managers use motivation in the workplace to inspire people to work, both individually and in groups, to produce the best results for business in the most efficient and effective manner. in this study, the researcher will focus on the application of motivational theory proposed by Kenneth A. Kovach. This is because Kovach's motivational theory are focusing on what employees want from their jobs with what their bosses though was important to the employees. The purpose of this study are to study whether Kovach's intrinsic motivational factors exist among employees at Petronas Refinery (Malacca) Sdn Bhd and to study whether extrinsic motivational factors highlighted by Kovach influence motivational level among employees at Petronas Refinery (Malacca) Sdn Bhd. The objectives of this study is to explain and investigates either Kovach's intrinsic and extrinsic motivational factor s exist and influence motivational level among employees at Petronas Refinery (Malacca) Sdn Bhd. The researcher will use sampling technique and using interview and questionnaires distribution method in order to obtain information. By competing this study, the researcher hope will give recommendations and using findings/results to help Petronas Refinery (Malacca) Sdn Bhd to increase job satisfaction among their employees.